Orthogonal Experimental Design Method Based on Influencing Factor Analysis of Moisture Content in Metro Vehicle Air Compressor Outlet Pressure Air - LI Jianxing; LI Huaizhi (Chengshi guidao jiaotong yanjiu)
［Objective］ The pressure air dryness at the metro vehicle air compressor outlet is a very important indicator. If the water content in the pressure air is high, it will affect the performance of various air-using equipment, and thus affect driving safety. When the Shanghai Rail Transit Operation and Maintenance personnel inspected some vehicles on the flood season, they find that there is liquid water in the vehicle air supply pipeline, which is caused by the excessively high water content in the pressure air. Under the existing conditions, it is necessary to study how to adjust the maintenance strategy and thus improve the drying capacity of the air compressor during the flood season. ［Method］ Through orthogonal experimental design methods, an experimental scheme is designed to analyze the influencing factors of air moisture content at the outlet pressure of the air compressor, and a method of using the Taguchi method to analyze the data and determine the main influencing factors was given. ［Result & Conclusion］ By using this test plan to conduct experiments, we can analyze the main factors that affect the moisture content of the air at the outlet pressure of the train air compressor. Based on this conclusion, the operation and maintenance personnel can formulate a maintenance strategy for the train air compressor suitable for the flood season. This orthogonal test design method can also be extended to the improvement and optimization of the operation and maintenance strategies of other equipment in urban rail transit.